Correlation of interleukin-6 and C-reactive protein levels in plasma with the stage and differentiation of colorectal cancer: A cross-sectional study in East Indonesia. (February 2021) - Hidayat, Ferdian; Labeda, Ibrahim; Sampetoding, Samuel; Pattelongi, Ilham Jaya; Lusikooy, Ronald Erasio; Warsinggih,; Dani, M. Iwan; Mappincara,; Kusuma, M. Ihwan; Uwuratuw, Julianus Aboyaman; Syarifuddin, Erwin; Faruk, Muhammad
Abstract: Introduction: Tumors most often develop due to inflammatory factors, including inflammatory cells that produce cytokines and cytotoxic mediators that can stimulate malignant transformation. Knowing that interleukin-6 (IL-6) and C-reactive protein (CRP) factor into the development of colorectal cancer (CRC), we aimed to assess IL-6 and CRP's relationship with the stage and differentiation of CRC. Methods: In a sample of 46 patients with CRC, as confirmed by histopathological examination, plasma levels of IL-6 and CRP were measured from peripheral venous blood samples before surgery and examined using enzyme-linked immunosorbent assay. Results: Most patients were male (63.0%) and at least 50 years old (73.9%). A positive correlation emerged between stage of CRC and both plasma IL-6 ( r = 0.396, p = .003) and CRP ( r = 0.376, p = .005) levels, which the Kruskal–Wallis test indicated were highest in stage IV (IL-6: median = 25.80, p = .019; CRP: median = 34.10, p = .040). Plasma IL-6 levels (median = 25.80, p = .019) were higher in well-differentiated CRC, whereas plasma CRP levels (median = 34.10, p = .040] were higher in poorly differentiated tissue. Linear plotting revealed a linear relationship between plasma IL-6 and plasma CRP levels in patients with CRC. Conclusion: Because the stage of CRC significantly correlates with plasma IL-6 and CRP levels, IL-6 and CRP can serve as diagnostic factors in assessing the progress and prognosis of CRC. Highlights: Interleukin-6 (IL-6) and C-reactive protein (CRP) levels can indicate inflammation. Chronic inflammation affects the progression of colorectal cancer (CRC). An association exists between IL-6, CRP, and stage of CRC. IL-6 and CRP can be diagnostic factors in assessing CRC's progression.